Incidence of Hortaea werneckii in a tertiary care centre in Maharashtra - Mehta, Sakshi; Bhakre, Jayshree; Kante, Sharvani; Harbade, Mangala S.; Iravane, Jyoti A. (International Journal of Research in Medical Sciences, 2024)
Background: Hortaea werneckii, a melanized yeast-like fungus is the cause of Tinea nigra, a superficial dermatomycosis. The lesions are differential diagnosis of melanocytic lesions. Tinea nigra mainly affects people in the temperate or subtropical climates with well-demarcated, expanding, hyperchromic plaques on the palms or soles. Methods: Skin scrapings from various lesions with suspected fungal aetiology were received after clinical assessment and were subjected to laboratory procedures, including direct KOH (10%) analysis, culture on Sabouraud dextrose agar (SDA), and incubation at 25°C and 37°C for 28 days which was further confirmed by lactophenol cotton blue preparation and slide culture. Results: Out of 295 samples examined, a total number of 15 samples were positive for Hortaea werneckii in the time period of 1st January 2023 to 31st December 2023. 7 patients had lesions on both palmar as well as plantar region (46.66%), 3 on palmar and plantar region each (20%), 1 (6.66%) on scalp and 1 (6.66%) on face and scalp. The skin scrapings were taken and examined in 10% KOH wet mount which showed positivity of 11 (73.33%) samples. The primary isolation of the fungus was done on SDA. Conclusions: Hortaea werneckii is the most common cause of Tinea nigra. Pigmented patches of Tinea nigra may be confused with other inflammatory or neoplastic aetiology. For Tinea nigra, skin scrapings are sufficient for diagnosis by KOH mount and culture on SDA. Generally, the lesions resolve within 2 weeks of adequate treatment. To conclude, a high suspicion should be maintained to timely diagnose the disease, avoid unnecessary invasive investigation and early administration of treatment.